First-principles studies concerning optimization of hydrogen storage in nanoporous reduced graphite oxide - Robledo, Carla Belén (2014)
By means of Density Functional Theory (DFT) calculations we investigated the optimal pore size for reduced graphite oxide (GOH) to favor hydrogen storage and to prevent oxygen interference. The interlayer distance of GOH is found to increase with oxygen content, given by the number of hydroxyl groups. Four types of GOHs were considered, with O/C ratio within a 0.09–0.38 range. In the case of the highest O/C ratio considered, 0.38, a spontaneous redox-reaction between hydroxyl groups delivering a water molecule and an epoxy group was found. Thus, GOHs with high O/C ratio are not recommended for hydrogen storage. In these materials the absorption energy values of hydrogen is in the range of −0.2 and −0.5 eV/molecule, that is within the values expected to allow an efficient storage. The best GOH for hydrogen storage was found to be that with a 0.09 O/C ratio since it has the largest void space and adequate absorption energy, −0.52 eV/molecule. On the other hand, oxygen absorption energy is lower in absolute value than that of hydrogen, which favors absorption of the latter, thus creating adequate conditions for its storage without oxygen interference.